Features of the Composition, Release, Localization, and Environmental Effects of Free Gases in the Khibiny Massif (Kola Peninsula, Northwest Russia): A Review - Valentin A. Nivin (Geosciences, 2025)
The article presents a comprehensive analysis of long-term studies on hydrogen-hydrocarbon free gases (FGs) in the rocks of the Khibiny massif, systematically organized and generalized for the first time. Gasometric observations were predominantly conducted within underground mine workings, with occasional measurements taken during the drilling of exploration boreholes at the surface or in subsurface air within loose sediments. Methane is the primary component of these gases, followed in descending order by hydrogen, ethane, helium, other methane homologs, and alkenes. Nitrogen is also presumed to be present, although its proportions remain undefined. The carbon and hydrogen in FGs exhibit relatively heavy isotopic compositions, which progressively lighten from methane to ethane. The intensity of gas emissions is characterized by a gas flow rate from shot holes and boreholes, reaching up to 0.5 L/min but generally decreasing significantly within an hour of reservoir exposure. Gas-bearing areas, ranging in size from a few meters to tens of meters, are distributed irregularly and without discernible patterns. The FG content in rocks and ores varies from trace amounts to approximately 1 m3 of gas per cubic meter of undisturbed rock. These gases are primarily residual, preserved within microfractures and cavities following the isolation of fluid inclusions. Their distribution and composition may fluctuate due to the dynamic geomechanical conditions of the rock mass. The release of flammable and explosive FGs presents a significant hazard during ore deposit exploration and development, necessitating the implementation of rigorous safety measures for mining and drilling operations. Additionally, the environmental implications and potential applications of gas emissions warrant attention. Future comprehensive studies of the Khibiny gases using advanced methodologies and equipment are expected to address various scientific and practical challenges.